The Strategy of Indonesian Diplomacy Efforts and National Political Interests in the Ethnic Rohingya Refugee Conflict - Hana Dwi Suwandari; Sugito Sugito (Indonesian Journal of Economics, Social, and Humanities, 2021)
The tragedy of ethnic Rohingya stems from the discriminatory treatment experienced decades ago in Myanmar. The lack of attention from the international community and humanitarian aid efforts for the Rohingya ethnic group in Myanmar has resulted in the wave of refugees fleeing from Myanmar to other countries is increasing, causing a sense of insecurity and instability in the region, especially South and Southeast Asia. This article aims to look at Indonesia's diplomacy strategy and Indonesia's national interests in the ASEAN region towards resolving the Rohingya ethnic conflict. This research observes Indonesia's national interest in this issue using a realism approach. The research was conducted using qualitative methods through literature studies and These data are analyzed, then described, or interpreted to obtain a complete picture of the answers to the problems under study. The results of the study found that the Indonesian government used a humanitarian diplomacy strategy as a bridge towards resolving cases of the Rohingya ethnicity in Myanmar. It was also found that Indonesia's interests in resolving Rohingya ethnic refugees have an interest in the security and political aspect, not just morality. Indonesia's humanitarian diplomacy role as a driver of democracy has been well received not only by the junta community but also by the international community.